Cereals as ‘leftover biomass’ : an analysis of Swedish cereal production from the perspective of feed-food competition - Tillgren, Beatrice (SLU/Department of Molecular Sciences, 2021)
In a time with climate change and a growing population it is important to use the arable land as effectively as possible to ensure food security and minimize environmental impacts. Currently, livestock production uses 70% of all agricultural land which highlights the competition between the usage of land for crops for feed rather than for human consumption. The overarching aim of this thesis is to analyse Swedish cereal production from the perspective of feed-food competition. The objective is to understand to what extent cereals produced in Sweden can be considered a left-over biomass, that is, unsuitable for human consumption and the reasons for that. The present work looked at current use of Swedish cereals as well as the quality criteria for food and feed cereals. This study shows that most of the cereals produced in Sweden are used for feed and that a great extent of the cereals used for feed reaches food quality. However, this is not to say that all cropland that is currently used to grow cereals for feed could instead be used to grow cereals that will reach the current quality criteria. This study has shown the current quality criteria used for cereals could be lowered in some aspects for cereals that are going to be used for example food-grains and groats. The conclusion of this study is that the amount of cereals that can be considered truly a leftover biomass, from growing cereals for human consumption, is small in Sweden.